Community composition in mangrove ponds with pulsed hypoxic and acidified conditions. Issue 12 (28th December 2017) - Gedan, Keryn B.; Altieri, Andrew H.; Feller, Ilka; Burrell, Rebecca; Breitburg, Denise
Abstract: The potential resilience of biological communities to accelerating rates of global change has received considerable attention. We suggest that some shallow aquatic ecosystems, where temperature, dissolved oxygen (DO), and pH can exhibit extreme variation on short timescales of hours or days, provide an opportunity to develop a mechanistic understanding of species persistence and community assembly under harsh environmental conditions. Extreme diel swings in DO and pH have been observed in eutrophic temperate ecosystems, and here, we describe a similar phenomenon consistently occurring across tropical sites that included relatively remote atolls on the Meso‐American barrier reefs in Belize and oligotrophic coastal lagoons in Panama. In particular, we documented large daily swings in temperature, DO, and pH within shallow ponds of Caribbean mangrove forests. Water in seven of 13 ponds went hypoxic (<2 mg/L DO) during the multiday sampling period, and pH dipped nightly to low levels, falling below 7.0 in some ponds. Minimum pH and minimum DO were correlated, and showed a similar relationship in Belize and Panama, suggesting a common mechanism produced diel cycles. Remarkably, most ponds exhibited high abundance of macroalgae, macroinvertebrates, and fish, despite potentially stressful abiotic conditions. Although fish diversity was negatively correlated with pH range, our overall results from the ponds suggest that many species are sufficiently resistant such that a functionally complex community can persist in the midst of pulsed stressful conditions. We propose that the mangrove ponds could serve as a model ecosystem for investigating resistance and resilience of coastal marine communities to global change factors such as climate change, hypoxia, and ocean acidification.